Exploring co-occurring conditions in Iraqi children with autism spectrum disorder: prevalence, characteristics, and potential risk factors - Toman, Ahmed Kamil; AbdulRasool, Hulla Raoof; Lami, Faris; Jasim, Shatha Mohammed; Jaber, Osamah Abbas; Nayeri, Nahid Dehghan; Sabet, Mahdi Shafiee; Al-Gburi, Ghaith (Frontiers in Psychiatry, 2025)
IntroductionCo-occurring conditions are common in children with autism spectrum disorder (ASD) and have important negative impacts on the children and their families. For Iraqi children, local healthcare systems tend to place more emphasis on the management of ASD itself while neglecting co-occurring conditions.ObjectivesThis study aims to investigate the prevalence, characteristics, and potential risk factors of co-occurring epilepsy, sleep, and weight issues among Iraqi children with ASD.MethodsA multicenter cross-sectional study was conducted from January 24 to August 7, 2024, including children from Imam Hussein Centre, Al-Subtain Academy for Autism and Neurodevelopmental Disorders, and Baghdad’s National Centre for Autism and Child Psychiatry. A structured questionnaire was used, including 35 items for demographic information, epilepsy, sleep problems, and weight issues.ResultsOur sample included 240 children, of whom 34 (14.2%) had co-occurring epilepsy, 178 (74.2%) had at least one sleep problem, and 104 (43.3%) were obese. Among children with epilepsy, 18 (52.9%) received their diagnosis before ASD. The most prescribed anticonvulsant, sodium valproate, was noted in 18 (52.9%) cases. Difficulty falling asleep was the most common sleep problem, affecting 97 (40.4%), while sleepwalking was reported in only 26 (10.8%). Significant differences in the body-mass index were observed based on risperidone use (adjusted p-value = 0.036, R-value = 0.163, 95% CI: 0.031, 0.288), sleep duration (r = -0.166, adjusted p-value = 0.036), and diet (adjusted p-value = 0.036, ϵ2 = 0.038, 95% CI: 0.005, 0.087). However, no significant association was demonstrated between BMI and screen time (adjusted p-value = 0.264).ConclusionCo-occurring conditions are common among children with ASD and should be assessed simultaneously. Additionally, since some of the children might be diagnosed with epilepsy first, it is important to consider co-occurring ASD in their diagnosis.